The Structure of Ambiguity Phenomena (Based on Cognitive Analyses of the Ways in Which Politicians Communicate) - Dobrosz-Michiewicz, Karolina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The paper presents the ambiguity phenomena in terms of cognitive categorization and blending processes. The analyses of politicians’ programme speeches, based on Lakoff’s and Langacker’s semantics and Langacker’s grammar research, result in describing the ambiguity phenomena as sender’s or receiver’s mental concepts rather than relating it to linguistic properties of the message. Moreover, a cognitive point of view in the research on ambiguity reveals its multilevelled structure, which stems from the polysemic nature of mental categories and blends.